ANALISIS YURIDIS TERHADAP KERJASAMA PEMBANGUNAN INFRASTRUKTUR MELALUI POLA PUBLIC PRIVATE PARTNERSHIP (PPP) - Eric Tanaka; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (Universitas Sumatera Utara, 2018)
Abstract The Indonesia Government can only meet 30% of infrastructure development fund that is needed, which are around 1.433 Trillion Rupiah from 4.796 Trillion Rupiah. Which means, there is a shortage of funding which the Indonesia Government is targeting around 36% of its infrastructure development fund us expected to be achieved by using of the one of the alternative funding sources and that is Public Private Partnership (PPP) which can be done which a private business entities in the country or foreign, state-owned enterprises or even union. PPP is not only expected to meet the shortage of funds, but it is also expected to provide knowledge and experience in development, operation, and management of the adequate infrastructure. However, in practice, PPP still encounters many hindrance. The technocratic work of PPP has not been fully able of penetrating the national infrastructure market and industry, and has not effectively overcome the hindrance in terms of regulation, institution and financing. This theses uses descriptive normative legal research, which prioritized primary data in the form of primary, secondary, and tertiary legal materials. This study refers to the main legal material by examining the theorises, concepts, legal principles, and legislation related to this research. The result show that law construction of PPP in Indonesia is generally regulated in Presidential Regulation 38/2015 concerning Government Cooperation with Business Entitites in Provision of Infrastructure in which regulate the types of infrastructure that are allowed to be built through the PPP. Generally, PPP financing scheme in Indonesia uses BOT concession contracts, which Government is obliged to provide land that are needed for infrastructure development and private parties who will spend funds to build the infrastructure. In case of dispute in the PPP agreement, the dispute resolution process will be conducted through mediation, conciliation, and arbitration. Keyword: Public Private Partnership (PPP), Build Operate Transfer (BOT).